Optimization of inductance multiplier parameters - Lishchynska, L. B.; Bulyha, I. V.; Voitsekhovska, O. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The method aimed at increase of inductance multiplication factor using generalized emittance transformer as optimum inductance multiplier is developed.